(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article analyzes the ethical and aesthetic concept concept of Ch. Aitmatov in his deep and multifaceted works on the theme of war. His works reflect not only the exploits of soldiers in war, but also the value of human life, the strength of the human spirit, which allows one to maintain high human qualities despite difficult circumstances. It is noted that the combination of epic scale and subtle lyricism in the creation of Aitmatov’s images has a greater impact both on the emotional level and on the intellectual one.